The Educational Orientation of Malaysia: The P.I.E.S Element of a Balanced Person in The National Education Philosophy (NEP) : (The Perspective of Islam Through the Interpretation of Sayid Qutb) - Hamid, Nur Bakri Abd; Alam, Naufal Ahmad Rijalul (Idarah (Jurnal Pendidikan dan Kependidikan), 2022)
Abstract: Through educational institutions, Malaysian education is focused on producing competitive human capital. The physical, intellectual, emotional, and spiritual models are the realization of Malaysia's educational goal in the assessment of the national education philosophy (PIES). This study investigates the PIES (physical, intellectual, emotional, and spiritual) ideas that have been formed in the National Education Philosophy and compares them to the Qur'an (NEP). This study, which analyzes the P.I.E.S. Master Book, the Fi Zilalil Qur'an, as well as narrative texts and articles on NEP, is qualitative. The findings demonstrated that Sayid Qutb's perspective on self-balance views it as having developed critical, balanced, and competent knowledge. The NEP review strengthens the connection between spiritual and physical, intellectual, emotional, and emotional qualities. To generate highly educated, civilized, reliable, competent, and skilled people to pursue lifetime educational leadership into the 21st century, all persons and parties concerned must follow the NEP paradigm. The PIES philosophy model's structure is essential to raising educational standards in Malaysia. Practical ramifications for those working in the field of education, including religious instructors, educators, writers, planners, and implementers of universal education. Abstrak: Orientasi pendidikan di Malaysia adalah menghasilkan modal manusia kompetitif melalui lembaga pendidikan. Realisasi terhadap capaian visi pendidikan Malaysia dalam tinjauan filsafat pendidikan nasional adalah model jasmani, intelektual, emosional dan spiritual (PIES). Penelitian ini merupakan pandangan dan pembahasan dibandingkan Al-Qur'an yang mendalami konsep Jasmani, Intelektual, Emosional, dan Spiritual (PIES) yang telah ditetapkan dalam National Education Philosophy (NEP). Kajian ini merupakan kajian kualitatif melalui analisis isi dari buku Master P.I.E.S, Fi Zilalil Qur'an dan teks naratif serta artikel yang membahas tentang NEP. Hasil penelitian menunjukkan komponen keseimbangan diri melalui perspektif Sayid Qutb adalah berkembangnya pengetahuan yang kritis, seimbang, dan mumpuni. Tinjauan NEP mengarah kepada penguatan integrasi nilai jasmani-intelektual-emosional dan spiritual. Semua individu dan pihak yang terlibat perlu mempraktekkan paradigma NEP untuk menghasilkan orang-orang berilmu dan bertakwa yang berpendidikan tinggi, beradab, amanah, dan memiliki keterampilan yang sangat baik untuk mengeksplorasi kepemimpinan pendidikan seumur hidup di luar abad ke-21. Konstruk model filosofi PIES berperan krusial terhadap peningkatan mutu pendidikan di Malaysia. Implikasi praktis bagi praktisi pendidikan yang terdiri dari guru agama, pendidik, penyusun, pemimpin, dan pelaksana pendidikan universal.